Vessel element and fiber length variation in successive cambia of Iresine latifolia (Amaranthaceae) - Silvia Zumaya-Mendoza; Teresa Terrazas (Revista Mexicana de Biodiversidad)
The size of the axial cell elements of wood, vessel elements and fibers, increases or decreases from pith to stem periphery in the species that have been studied with successive cambium such as members of the Menispermaceae. Iresine latifolia (Amaranthaceae) was selected for this study because it is a scandent shrub widely distributed in Mexico with successive cambia. The objectives were to quantify vessel element and fiber lengths in each of the vascular rings, to evaluate whether cellular size increases or decreases from pith to periphery, and to describe its wood. Macerations were performed for each of the secondary xylem rings present in 3 individual samples, and permanent slides were prepared using conventional procedures for wood. Observations showed that I. latifolia has 13–36 concentric rings, each ring showing an active cambium. Like other species of Amaranthaceae, there are nucleated fibers and multiseriate rays with a meristematic center. Variance analyses showed significant differences between vessel element and fiber lengths between only some of the vascular rings from pith to periphery. These results suggest that the parenchyma cells, from which the new cambium is derived, reach the size of the fusiform initial cells early in the differentiation process.